FROM TOUCH TO NARRATIVE: DIGITAL IMMERSIVE TECHNOLOGIES IN INTEGRAL DEVELOPMENT DURING CHILDHOOD - Borges, Martinha Luiza Rolim de Moura (Seven Editora, 2026)
This research aimed to reflect on recent scientific production, through a narrative literature review, regarding the use of immersive digital technologies, focusing on tactile interaction and narrative construction, to understand their contribution to the integral development of children in early childhood education. Based on a qualitative, exploratory approach, a narrative literature review was conducted in the following databases: Scopus; Web of Science; Scientific Electronic Library Online (SciELO); Google Scholar; Portal de Periódicos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES); and Biblioteca Digital de Teses e Dissertações (BDTD). From the searches, studies published between 2015 and November 2025 were selected, with an emphasis on scientific articles, dissertations, theses, books, and institutional documents that discussed the educational potential of digital technologies in childhood. The results indicated that the pedagogical use of immersive environments, such as augmented reality (AR) and virtual reality (VR), expands children's cognitive, motor, social, and emotional experiences, favoring active exploration, problem-solving, peer communication, and creative expression, in addition to contributing to the development of symbolic, creative, and communicative skills. However, theoretical gaps persisted regarding teacher mediation, the ethical limits of technological use, and unequal access to digital resources. It was concluded that the intentional, critical, and mediated use of immersive technologies can contribute to a pedagogy sensitive to childhood, based on playfulness, interaction, and inclusion, consistent with the formative and sociocultural demands of the digital age.DOI: https://doi.org/10.56238/sevened2026.001-006